2004
DOI: 10.1111/j.1468-0297.2004.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

How Important is Methodology for the Estimates of the Determinants of Happiness?

Abstract: Psychologists and sociologists usually interpret happiness scores as cardinal and comparable across respondents, and thus run OLS regressions on happiness and changes in happiness. Economists usually assume only ordinality and have mainly used ordered latent response models, thereby not taking satisfactory account of fixed individual traits. We address this problem by developing a conditional estimator for the fixed-effect ordered logit model. We find that assuming ordinality or cardinality of happiness scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

96
1,287
1
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,384 publications
(1,401 citation statements)
references
References 74 publications
96
1,287
1
17
Order By: Relevance
“…The first ones assume that the answers to well-being questions are cardinal, while the second type of techniques only assume ordinality. Ferrer-i-Carbonell and Frijters (2004) show that assuming cardinality or ordinality generates similar results in terms of the trade-offs between variables, which is the information we use in this paper. The first measure of well-being (see Figure 1 in section 'Survey questions') is regressed by means of an ordered probit (OP).…”
Section: Econometric Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…The first ones assume that the answers to well-being questions are cardinal, while the second type of techniques only assume ordinality. Ferrer-i-Carbonell and Frijters (2004) show that assuming cardinality or ordinality generates similar results in terms of the trade-offs between variables, which is the information we use in this paper. The first measure of well-being (see Figure 1 in section 'Survey questions') is regressed by means of an ordered probit (OP).…”
Section: Econometric Methodsmentioning
confidence: 64%
“…Subjective questions on self-reported well-being have been used in economics to understand and explore a large range of interesting topics, such as unemployment, health, job situation, and income (Blanchflower and Oswald, 2004;Clark and Oswald, 1994;DiTella et al, 2001;Easterlin, 2001;Ferreri-Carbonell, 2005;Ferrer-i-Carbonell and Frijters, 2004;Ferrer-i-Carbonell and Van Praag, 2002;Frey and Stutzer, 2002;Frijters et al, 2004;Oswald, 1997;Van Praag and Ferrer-i-Carbonell, 2004). In doing so, economists take individuals answer to well-being questions as a proxy to measure utility (see, e.g.…”
Section: The Well-being Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[ Table 3 (Ferrer-i-Carbonell and Frijters;Schmitz, 2011). Although a random effects model is a possible alternative specification, a Hausman test revealed that this alternative is not supported by the data and that a fixed effect model is therefore preferred.…”
Section: [Table 2]mentioning
confidence: 99%
“…The strength of FE models is that they remove unobserved, time-invariant confounding, and as a result have been recommended for studying both the impacts of alcohol (French & Popovici, 2011) and influences on wellbeing (Ferrer-i-Carbonell & Frijters, 2004). In Study 1, we use FE analyses of a conventional cohort dataset with gaps of several years between waves.…”
Section: Study 1: Cohort Data Methods Designmentioning
confidence: 99%